2005
DOI: 10.1080/02713680590934067
|View full text |Cite
|
Sign up to set email alerts
|

Intraretinal pH in Diabetic Cats

Abstract: While the number of animals is small, we conclude that the [H+](O) distribution varied from normal to damaged in the same retina. Diabetes seems to lead to an acidification of the inner retina that appears to be at least partly related to hyperglycemia and which may be important in the progression of retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
1
23
1
Order By: Relevance
“…Next to rodents, cats and dogs have been used most extensively as models of diabetic retinopathy and they provide excellent models of early-stage clinical disease (Budzynski et al, 2005;Gardiner et al, 2003b;Gardiner et al, 1994;Hatchell et al, 1995;Linsenmeier et al, 1998;Mansour et al, 1990). Dogs have been most extensively used for retinopathy studies with diabetes commonly induced using chemical induction of diabetes (Anderson et al, 1993) (Figure 6).…”
Section: Modelling Diabetic Retinopathymentioning
confidence: 96%
See 1 more Smart Citation
“…Next to rodents, cats and dogs have been used most extensively as models of diabetic retinopathy and they provide excellent models of early-stage clinical disease (Budzynski et al, 2005;Gardiner et al, 2003b;Gardiner et al, 1994;Hatchell et al, 1995;Linsenmeier et al, 1998;Mansour et al, 1990). Dogs have been most extensively used for retinopathy studies with diabetes commonly induced using chemical induction of diabetes (Anderson et al, 1993) (Figure 6).…”
Section: Modelling Diabetic Retinopathymentioning
confidence: 96%
“…For example, a number of in vitro studies and in vivo investigations of animal models and human post-mortem specimens indicate that activation of retinal microglia could play an important regulatory role in diabetes-mediated retinal inflammation (Zeng et al, 2008) by modulating cytokine expression (Budzynski et al, 2005) and other pathologic responses (Kuiper et al, 2004). Monocytes that infiltrate the retina are distinct from microglia and they reside in proximity to blood vessels (perivascular macrophages) or within various layers of the neuropile (Xu et al, 2009).…”
Section: D Inflammation and Immune Cell Activation In Diabetic Retimentioning
confidence: 97%
“…This characteristic allows good evaluation of the fundus for study of diabetic retinopathy. Using retinal photography and fluorescein angiography every 6 mo over a 9-yr period, pancreatectomized cats maintained with poor glycemic control (blood glucose 200-400 mg/dL) developed many of the retinal abnormalities common in diabetic retinopathy in humans (Budzynski et al 2005;Hatchell et al 1995;Linsenmeier et al 1998). The changes included early nonleaking microaneurysms, scattered punctuate intraretinal hemorrhages, capillary nonperfusion, and possibly neovascularization.…”
Section: Diabetic Retinopathymentioning
confidence: 96%
“…Still, the inner retina in diabetic cats tends to be acidotic compared with that of healthy cats. 44 One must be cautious about extrapolating from shortterm hyperglycemia to the more complex situation in diabetes. However, in light of the large hyperglycemiainduced inner retinal pH changes observed in this study, the inner retinal acidosis previously observed in diabetic cats, 43 and the observation that acidosis alone can induce retinopathy, [37][38][39] we conclude that pH changes may play a role in the development and progression of diabetic retinopathy in humans.…”
Section: Angiogenesismentioning
confidence: 99%